Lemon curd killer - Childs, Laura (Childs, Laura. Tea shop mystery, 2024)
"High tea and high fashion turn deadly in this latest installment of the New York Times bestselling series. Tea shop entrepreneur Theodosia Browning has been tapped to host a fancy Limón Tea in a genuine lemon orchard as a rousing kickoff to Charleston Fashion Week. But as fairy lights twinkle and the scent of lemon wafts among the tea tables, the deadly murder of a fashion designer puts the squeeze on things. As the lemon curd begins to sour, the murdered woman's daughter begs Theodosia to help find the killer. Tea events and fashion shows must go on, however, which puts Theodosia and her tea sommelier, Drayton Conneley, right in the thick of squabbling business partners, crazed clothing designers, irate film producers, drug deals, and a disastrous Tea Trolley Tour"--